Transcatheter Heart Valve Thrombosis in a Patient With Polycythemia Vera Despite Apixaban Therapy for Atrial Fibrillation - Gauranga Mahalwar, MD; Nicole Lao, MD; Arslan Babar, MD; Samir R. Kapadia, MD; Ankur Kalra, MD; David Cutler, MD; Per Wierup, MD (JACC: Case Reports, 2021)
We present a case of transcatheter heart valve thrombosis in a 76-year-old man with paroxysmal atrial fibrillation on therapeutic anticoagulation with apixaban and polycythemia vera. The incidence of transcatheter heart valve thrombosis in patients with atrial fibrillation and on adequate anticoagulation is not well reported. (Level of Difficulty: Intermediate.)